Curiosity-Driven Learning in Arabic: A Case Study on the 'Inquiring Minds Want to Know' Approach - dewi, intan; Ahmad Nurcholis,; Izzatul Laila,; Juan Acevedo,; Moumen El-Sayed, (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2025)
This study aims to analyze the implementation of the "Inquiring Minds Want to Know" learning model in Arabic language instruction at MTsN 3 Tulungagung. The model was chosen to address the gap between students' desire to learn and their ability to cultivate curiosity. This research employed a phenomenological qualitative approach, utilizing interviews, observations, and documentation for data collection. The findings reveal that the implementation of the "Inquiring Minds Want to Know" learning model in Arabic language instruction follows four main stages: (1) formulating questions that stimulate students' interest in learning and discussion, (2) providing opportunities for students to make predictions or guesses, (3) recording all student predictions without immediately providing answers to maintain curiosity, and (4) using questions as a bridge to connect learning materials and delivering appropriate answers throughout the learning process. This learning model has proven effective in enhancing students' active participation and critical thinking skills in the context of Arabic language learning.